Ibn Khaldun's Islamic Educational Thought: Relevance in the Modern World - Siti Mahmudah; St. Nurhayati Ali; Ridwan (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This research examines Ibn Khaldun's Islamic educational thought and its relevance to the challenges of the modern world. The main problem raised in this study is how the educational concepts put forward by Ibn Khaldun, especially in Muqaddimah, can be applied in the contemporary education system that faces the challenges of globalization, digitalization, and moral crisis. The purpose of this research is to analyze the concept of Ibn Khaldun's education, identify aspects that are still relevant to modern education, and offer implementation strategies in the current learning system. This study uses a qualitative method with a textual analysis approach to Ibn Khaldun's works as well as case studies that are relevant in modern education. The results of the study show that the concept of Asabiyyah or social solidarity has important implications in creating an inclusive and collaborative learning environment. In addition, Ibn Khaldun's thoughts on gradual education and character formation are very relevant in building an education system that is not only academically oriented, but also on strengthening the morals and ethics of students. The conclusion of this study confirms that Ibn Khaldun's Islamic educational thinking can be a solution in facing the challenges of modern education. By adapting Islamic educational values into technology-based learning systems, character education, and community-based approaches, a more holistic and sustainable model of education can be realized. This research contributes to the development of an education system that is able to answer the needs of the times without losing fundamental Islamic values.